2006
DOI: 10.1103/physrevlett.97.176803
|View full text |Cite
|
Sign up to set email alerts
|

Double-Dot Quantum Ratchet Driven by an Independently Biased Quantum Point Contact

Abstract: We study a double quantum dot (DQD) coupled to a strongly biased quantum point contact (QPC), each embedded in independent electric circuits. For weak interdot tunneling we observe a finite current flowing through the Coulomb blockaded DQD in response to a strong bias on the QPC. The direction of the current through the DQD is determined by the relative detuning of the energy levels of the two quantum dots. The results are interpreted in terms of a quantum ratchet phenomenon in a DQD energized by a nearby QPC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 21 publications
10
147
1
Order By: Relevance
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
“…The QPC bias is chosen sufficiently small to avoid back-action on the QD. 19,20 The QD is coupled to source and drain electrodes via two tunneling barriers which can be separately controlled with gate voltages V G1 and V G2 . These gates are also used to tune the number of electrons on the QD.…”
Section: Figmentioning
confidence: 99%
“…The process induces a current flow through the system. Since the detuning δ may be varied continuously by applying appropriate gate voltages, the absorbtion energy is fully tunable.The scheme is experimentally challenging, due to low current levels and fast relaxation processes between the QDs [10]. Here, we show that these problems can be overcome by using time-resolved charge-detection techniques to detect single electrons tunneling into and out of the DQD.…”
mentioning
confidence: 99%